The feminization of poverty: A critical analysis of Bones (1988) and The Uncertainty of Hope (2006). - Dube, Faith (Midlands State University, 2017)
Zimbabwean literature is characterised by aspects that affect the society at different levels. The feminization of poverty is one of the many social ills that are depicted in the different works of art. The purpose of this study is to highlight through the different feminist views why poverty has a female face in Zimbabwe right from the colonial up to the post independent period. Through the critical comprehension of Bones (1988) and The Uncertainty of Hope (2006), the analysis draws into consideration that male and female feminist writers differ in their handling of the feminisation of poverty in Zimbabwe. The options, opportunities and solutions that they give to their female and male characters that are languishing in poverty are different, but the fact remains that poverty has a female face in Zimbabwe.